Challenging The City Scale, Helsinki (2018)
Walking into Haukilahti High School, you could easily believe that you have entered the wrong place. There are some adolescents in the main hall, sitting on Fatboy pouffes or at the table of a Korean restaurant. But there’s no reception desk, no loud playground, no timetable, no uniform or anything that would remind you of a traditional school. “Are you waiting for me?” asks Professor Jarmo Suominen when he arrives. Obviously, we are in the right place. A teacher of architecture and design, Jarmo Suominen is one of the main initiators of this school, which is unlike any other. He calls it “school as a service”, versus “school as a product”. What does it mean? In the same way that city dwellers tend to use mobility rather than own a car, the school building is not owned by the city of Espoo but rented. It is situated in the heart of Aalto University’s Otaniemi campus, one of the largest in Finland. Our meeting with Jarmo Suominen took place in the main building of Haukilahti High School, but all the teaching is spread around the campus’s facilities: physics in the university’s chemistry department, sports on the football pitches, drawing in the visual arts building... Even the school’s career services aren’t in the main building, but are located elsewhere on campus. For lunch and coffee, students go to places like the Korean restaurant. Run by a Finnish lady who used to live in Seoul, it offers meals like Korean bibimbap–much healthier and tastier than what you would find in a classical school canteen.